IQ and hemizygosity for the Val158Met functional polymorphism of COMT in 22q11DS. Issue 8 (13th September 2016) - Franconi, Colleen P.; McDonald‐McGinn, Donna; Zackai, Elaine H.; McNamara, Meghan A.; Salmons, Harold; Moss, Edward; Gur, Raquel E.; Devoto, Marcella; Emanuel, Beverly S.
Abstract : 22q11.2 Deletion Syndrome (22q11DS) is a multisystem disorder caused by a hemizygous deletion within 22q11.2. Patients with the deletion display a wide range of cognitive deficits. The gene catechol‐O‐methyl‐transferase (COMT) resides in the typically deleted region of 22q11.2 and is rendered hemizygous in individuals affected by the 22q11DS. COMT is a critical enzyme in the degradation of catecholamine neurotransmitters in the brain. A functional polymorphism, Val 158 Met, has been associated with a variety of neurocognitive outcomes. In this study, 159 patients with 22q11DS were analyzed for a potential association between intelligence quotient (IQ) and COMT genotype. We performed a univariate analysis for overall influence and modified our analysis to focus on possible differences between average, borderline, and intellectually impaired patients. No correlation between COMT genotype and IQ performance was found. © 2016 Wiley Periodicals, Inc.